2016
DOI: 10.1615/critreveukaryotgeneexpr.2016016525
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptides for Protein-Protein Interaction Targets: Applications to Human Disease

Abstract: Protein-protein interactions (PPIs) represent a significant portion of functionally relevant biological interactions, and therefore potential therapeutic targets. Small molecules were traditionally used to target PPIs. However, many PPI surfaces lack binding pockets due to their large and flat structures. Antibodies can also be used to modulate PPIs, but they are expensive and not cell permeable. Linear peptides are less expensive to produce than antibodies and are generally more selective than small molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…The increased potency of PTD1 toward WHSC1 when compared to PTD2 may indicate that optimization of PTD2 is also possible. Although peptides typically have poor stability and cell permeability [ 53 ], advances in the field of cyclic peptides [ 54 ] and modifications such as N-methylation [ 55 ] have been successfully utilized to increase bioactivity of peptides, and this could be a potential avenue for optimization of PTD2. The structure of WHSC1L1-PTD2 may also inspire structure-based approaches for drug discovery efforts towards the NSD family, for which PTD2 will be a valuable tool for in vitro assay development and validation.…”
Section: Discussionmentioning
confidence: 99%
“…The increased potency of PTD1 toward WHSC1 when compared to PTD2 may indicate that optimization of PTD2 is also possible. Although peptides typically have poor stability and cell permeability [ 53 ], advances in the field of cyclic peptides [ 54 ] and modifications such as N-methylation [ 55 ] have been successfully utilized to increase bioactivity of peptides, and this could be a potential avenue for optimization of PTD2. The structure of WHSC1L1-PTD2 may also inspire structure-based approaches for drug discovery efforts towards the NSD family, for which PTD2 will be a valuable tool for in vitro assay development and validation.…”
Section: Discussionmentioning
confidence: 99%
“…Conformational restriction of natural peptides has been used to identify active geometry and to enhance therapeutic potential by mitigating issues such as low oral availability and poor metabolic stability (Carney et al, 2014; Rubin and Qvit, 2016; Lubell, 2017). Since pioneering studies by Freidinger and Veber, the application of Agl residues has proven effective for constraining the backbone sequence to favor β-turn geometry in various peptides (Freidinger et al, 1980, 1982; Yu et al, 1988; Zhang et al, 1996; Aube, 1999; Perdih and Kikelj, 2006; Valle et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4 Because of their size and complexity, macrocycles have demonstrated that they can bind with antibody-like affinity and specificity and successfully target PPIs. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Hence, macrocyclic molecules fill an important gap in the world of drugs between small molecules and larger biologics. 19,20 Significant progress has been made for peptides in terms of synthesis, formulation and delivery, 21 but their therapeutic value is partially limited due to their short in vivo half-life and lack of oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%